Addendum: 2D homogeneous solutions to the Euler equation. Issue 3 (4th March 2017) - Luo, Xue; Shvydkoy, Roman
ABSTRACT: In this addendum note we fill in the gap left in the description of 2D homogeneous solutions to the stationary Euler system initiated in the previous publication. This completes the classification of all homogeneous stationary solutions. The note includes updated classification tables.